Character Values Workshop: Implementing Pancasila & Parental Readiness: Workshop Nilai Karakter: Implementasi Pancasila & Kesiapan Orang Tua - Tirtoni, Feri; Susilo, Joko; Astutik, Ika Ratna Indra (Universitas Muhammadiyah Sidoarjo, 2023)
This qualitative descriptive study aims to explore educational independence efforts through free innovation and free thinking, alongside the analysis of parental participation in schools embracing local wisdom. By employing a data-driven approach, this study examines the reports obtained from online reference sources. The findings underscore the significance of character education derived from Indonesia's rich local wisdom. The implementation of local wisdom in everyday life not only ensures its enduring nature but also enables it to adapt to the evolving currents of the times. Furthermore, the study highlights the necessity of integrating local wisdom into state policies and emphasizes the crucial role of parents in instilling Pancasila values during early childhood. The results of this study provide valuable insights for researchers and policymakers seeking to strengthen moral values and address societal shifts in a global context. Highlights: Revitalizing moral values: Explore the role of educational independence and parental participation in reviving and strengthening Pancasila values. Unveiling local wisdom: Investigate the significance of local wisdom as a source for character education and its relevance in responding to societal changes. Implications for policy and early childhood: Highlight the need for integrating local wisdom into state policies and emphasize the importance of parental involvement in instilling Pancasila values during early childhood. Keywords: Pancasila Values, Educational Independence, Parental Participation, Local Wisdom, Character Education.